2018
DOI: 10.1111/ajt.14996
|View full text |Cite|
|
Sign up to set email alerts
|

Direct-acting antivirals are effective and safe in HCV/HIV-coinfected liver transplant recipients who experience recurrence of hepatitis C: A prospective nationwide cohort study

Abstract: Direct-acting antivirals have proved to be highly efficacious and safe in monoinfected liver transplant (LT) recipients who experience recurrence of hepatitis C virus (HCV) infection. However, there is a lack of data on effectiveness and tolerability of these regimens in HCV/HIV-coinfected patients who experience recurrence of HCV infection after LT. In this prospective, multicenter cohort study, the outcomes of 47 HCV/HIV-coinfected LT patients who received DAA therapy (with or without ribavirin [RBV]) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…HCV co-infection has negatively affected these results, as the cure rate with pegylated interferon and ribavirin was low. However, interferon-free DAAs have since changed this, and cure rates for LT are high, similar to those in HIV-negative recipients [9]. With HCV eliminated, the prognosis of liver and renal transplantation in HIV-infected patients is good (Table 1).…”
mentioning
confidence: 99%
“…HCV co-infection has negatively affected these results, as the cure rate with pegylated interferon and ribavirin was low. However, interferon-free DAAs have since changed this, and cure rates for LT are high, similar to those in HIV-negative recipients [9]. With HCV eliminated, the prognosis of liver and renal transplantation in HIV-infected patients is good (Table 1).…”
mentioning
confidence: 99%
“…In HIV/HCV‐coinfected LT recipients, high SVR rates (93.6%‐96.6%) were observed with DAA in stable patients treated late after transplant (median 12‐71 months after) . Nonetheless, the few patients with FCH (n = 6) included in the CUPILT cohort showed a slower virological response compared with the others (HCV‐RNA below the limit of quantification after 9 weeks in FCH vs 6 weeks in F3‐F4 and 4 weeks in F1‐F2), suggesting a more difficult‐to‐treat condition compared with stable patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genotype 4 patients appear to be underrepresented in the studies with SOF/VEL (5%) and GLE/PIB (4%), and in HIV/HCV‐coinfected LT recipients a trend to lower SVR rate compared with other genotypes (77.8% vs. 90.9%; P = .566) has been observed. Moreover, two cases of virological breakthrough have been described, even though with suboptimal regimen (simeprevir plus daclatasvir plus ribavirin) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, the introduction of direct-acting antivirals (DAAs) has completely changed treatment of HCV infection. Randomized control trials and real-life cohort studies based on HCV-mono-infected LT recipients have shown positive results in terms of efficacy and safety [11].…”
Section: Introductionmentioning
confidence: 99%